COVID-19 Highlights the Need for More Effective Wildlife Trade Legislation. (December 2020) - Borzée, Amaël; McNeely, Jeffrey; Magellan, Kit; Miller, Jennifer R.B.; Porter, Lindsay; Dutta, Trishna; Kadinjappalli, Krishnakumar P.; Sharma, Sandeep; Shahabuddin, Ghazala; Aprilinayati, Fikty; Ryan, Gerard E.; Hughes, Alice; et al.
Abstract : Zoonosis-based epidemics are inevitable unless we revisit our relationship with the natural world, protect habitats, and regulate wildlife trade, including live animals and non-sustenance products. To prevent future zoonoses, governments must establish effective legislation addressing wildlife trade, protection of habitats, and reduction of the wildlife–livestock–human interface.